HIPERREALITAS MEDIA SOSIAL DALAM FILM BLACK MIRROR EPISODE NOSEDIVE - Diah Natalia, Ni Kadek Ayu; Sugiarica Joni, I Dewa Ayu; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2019)
xABSTRACT8 Filmxhas strength in constructing people through symbols it sends by every scenes. Besides construction of meaning, film also has the power to manipulate reality. This is known as hyperreality. The basic conceptx usedx inx thisx researchx isx thex hyperreality theoryr by Jean Baudrillard. It is applied on the serial anthology Black Mirror episode Nosedive. The research method is to observe the whole film content and to analyse each and every signs, verbal and non-verbal, to find out their correspondence to Baudrillard thoughts, followed with exposition according to semiotic text analysis of Charles Sanders Peirce.The results show many signs in this film have strong relation with Baudrillard concept. Consequently it has pictorial potencies which can be determined as hyperreality phenomena. A society unawareness that live in a world of technological simulation and social interaction in accordance with algorithm preference. Keywords: FilmNosedive, Hiperreality, Jean Baudrillard, Social Media